Bis[diphenylphosphino]methane and its bridge-substituted analogues as chemically non-innocent ligands for H2 activation. Issue 14 (23rd January 2020) - Kireev, Nikolay V.; Filippov, Oleg A.; Gulyaeva, Ekaterina S.; Shubina, Elena S.; Vendier, Laure; Canac, Yves; Sortais, Jean-Baptiste; Lugan, Noël; Valyaev, Dmitry A.
Abstract : Interconversion between coordinated diphosphinomethane and diphosphinomethanide moieties can be used as a new tool for metal–ligand cooperation. Abstract : Deprotonation of fac -[(κ 2 P, P -Ph2 PCH(R)PPh2 )Mn(CO)3 Br] (R = H, Me, Ph) produces the corresponding diphosphinomethanide derivatives fac -[(κ 3 P, C, P -Ph2 PC(R)PPh2 )Mn(CO)3 ], which are prone to activate H2 to form the hydride complexes fac -[(κ 2 P, P -Ph2 PCH(R)PPh2 )Mn(CO)3 H]. The substitution of the dppm bridge improves dramatically the reaction efficiency and this was rationalized by DFT calculations.